UJI COBA PENGGUNAAN BERBAGAI MACAM BAHAN BUBU UNTUK PENANGKAPAN LOBSTER DI DANAU MANINJAU - Eko Pramono Sipayung; Bustari '; Irwandy Syofyan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research was conducted on May 2016 at Maninjau village, Tanjung Raya sub district, Agam district, Sumatera Barat province. The purpose of this study to determine the effect of the manufacture of fishing gear traps made of bamboo, wood, and plastic nets for catching lobster in Lake Maninjau. The method used in this research is the method by conducting experiments obsrevasi spaciousness fishing. The results showed that the catch per trap did not differ much. Bamboo fish trap catches of 38 heads, 35 tails wood, plastic netting 34 and 34 tails. Calculation of ANOVA concluded, that difference does not affect the material trap catches of lobster, evidenced by the average value of Fhit <Ftab at 5% level that is Fhit 0.42 <Ftab 2.96.Keywords : Red Claw, bamboo trap, wood trap, jarring trap, plastic trap, Lake Maninjau Waters